UPAYA PENINGKATAN ENTREPREUNERSHIP MELALUI INISIASI DAN PELATIHAN PENGEMASAN WEDANG PUCUK DAUN JATI (TECTONA GRANDIS L.F) - Suwahono Suwahono (Universitas Muhammadiyah Semarang, 2017)
The entrepreneurial spirit and value can be influenced through the initiation process, and business training. pharmacological analysis of teak shoots(Tectona Grandis l.f) had antibacterial, antioxidant, antifungal, antiinflammatory,antipyretic, analgesic, anti-diuretic, and hypoglycemic activity.The use of teak leaves in the form of easy use should be disseminated andintroduced through initiation and entrepreneurship training. The results of thisstudied indicate had a significant influence betweeninitiation and training ofteak leaf packaging with the entrepreneurial spiritand value. Keywords: Enterpreneurship, Tectona Grandis L.F